INVESTIGATING THE IMPORTANCE OF FLOATING GRICE'S MAXIMS IN TRANSLATING ADVERTISEMENTS - Ayah Ismail Ibrahim; Asst. Prof. Dr. Maha Bakir Mohammed (American Journals Publishing, 2024)
This study investigates the application and implications of Grice's conversational maxims in the translation of deceptive expressions within advertisements. Specifically, it examines which maxim—quantity, quality, relation, or manner—is most frequently floated by translators. The study posits two hypotheses: first, that translators are more likely to float rather than violate these maxims, and second, that the maxim of quality is floated more frequently than the others. Findings partially support the first hypothesis, revealing that translators floated Grice’s maxims 13 times out of 27 instances to mitigate the impact of deceptive content, often altering the information quantity, message quality, relational context, and message order to maintain the source language text's (SLT) overall integrity and persuasive intent. However, the second hypothesis is refuted, as translators generally maintained adherence to the quality maxim, prioritizing honesty and commitment to the SLT’s intended meaning over floating it. These findings underscore the nuanced role of Grice’s maxims in achieving faithful and effective translation in advertising contexts, where rhetorical strategies often necessitate flexible adherence to these conversational principles.
Keywords: Floating, deceptive expressions, advertisements, translation, violation.